Relationship between Calcium Stone Disease and Metabolic Syndrome - Polat, Emre Can; Ozcan, Levent; Cakir, Suleyman Sami; Dursun, Murat; Otunctemur, Alper; Ozbek, Emin (Urology Journal, 2015)
Purpose: We aimed to investigate relationship between metabolic syndrome and calcium-oxalate stone formation. Materials and Methods: Between January 2008 and February 2015 we retrospectively investigated biochemical parameters and anthropometric characteristics (height, weight, and waist circumference) of 198 patients who had calcium-oxalate stones and we also randomly selected 200 participants who had no history of urolithiasis as the controls. Results: The presence of obesity increased the risk of calcium stones in both men (P = .003, OR = 2.92) and women (P = .03, OR = 2.18). Diabetes was significantly correlated to the risk of calcium stones (P = .04, OR = 1.94). However, when calculated separately for men and women, diabetic men had a higher risk of calcium-oxalate stone disease (P = .04, OR = 2.59), but diabetic women did not (P > .05). Hypertension also significantly increased the risk of calcium stones when compared with normotensive individuals (P = .0001, OR = 3.03). Conclusion: The risk for the development of calcium-oxalate stone disease is most significantly associated with the patient's body mass index and the presence of hypertension.